Evaluasi Program Kartu Pedagang Produktif Bagi Usaha Mikro Kecil dan Menengah di Kabupaten Bojonegoro - Mutmainah, Mutmainah; Septian, Esa; Lukita, Cahya (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The Productive Merchant Card Program is an MSME empowerment program created by the Bojonegoro Regency Government. This program is made so that people who work as traders can prosper with the facilities provided by this program. However, in its implementation, there are problems, among others, that this program should provide capital loans with low interest without collateral, it turns out that there is a guarantee, the nominal liquid loan is reduced from the amount proposed, and it turns out that there are still people who do not understand how to use the card. The purpose of this study is to assess how far the Productive Merchant Card Program is realized for MSME actors and to find out what factors affect the implementation of the program. This study uses William N. Dunn's Evaluation theory which contains six achievement indicators, namely, Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. The method used is a descriptive qualitative method with a case study strategy. The results of this study found that the Productive Merchant Card Program has not fully achieved the expected target so in its realization it has not fully benefited MSME actors or traders.